Challenges and Opportunities in Strengthening Religious Moderation: A Psychological Study of Muslim Adolescents' Attitudes - Cahyandari, Rinova (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2025)
Religious moderation needs to be understood and implemented in national and state life. Problems in implementing religious moderation still occur in society. Efforts to strengthen religious moderation have been made, but preventive efforts, such as identifying individual attitudes, have not been studied. This paper aims to uncover adolescents' attitudes toward interfaith diversity using a descriptive, quantitative approach and an eight-question survey administered to 27 adolescents at a madrasah school. The results show that the majority of respondents exhibited inhibiting attitudes, including a tendency to worship excessively, a lack of friends or activities with people of different religions, a lack of opportunities to visit places of worship of other religions, and a tendency to avoid conflict without a solution. The majority of respondents also showed openness to making friends with people of different religions, to cross-checking information for fairness, and to understanding Islam that respects traditions as long as they do not conflict with Islamic law. This identification broadens the theoretical perspective on religious moderation, understanding it not only as cognitive learning but also as a socio-psychological process. These findings provide a mapping and recommendations for developing a tolerance-strengthening program to build a broad and sustainable ecosystem of religious moderation.